2021
DOI: 10.1021/acscatal.1c00538
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Experimental and Computational Hydrogen Evolution Activities of Pt(111) through DFT-Based Constrained MD Simulations

Abstract: The computational hydrogen evolution activity of Pt(111) remains controversial due to apparent discrepancies with experiments concerning rate-determining activation free energies and equilibrium hydrogen coverages. A fundamental source of error may lie within the static representations of the metal−water interface commonly employed in density functional theory (DFT)based kinetic models neglecting important entropic effects on reaction dynamics. In this work, we present a dynamic reassessment of the Volmer−Tafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 102 publications
5
49
0
Order By: Relevance
“…This process proceeds with a barrier of 0.67 eV to overcome the transition state (TS) located at an H−H separation distance of 1.05 Å. Our calculated barrier is in excellent agreement with recent constrained-AIMD calculations by Kronberg and Laasonen, 48 in which the barrier for the Tafel mechanism exhibits a coverage dependence, decreasing from 0.80 eV (0.66 ML) to 0.53 eV (1.00 ML). To validate the reliability of our calculated free energy, we compare the HDNN with AIMD simulations, resulting in a mean averaged error (MAE) of ∼0.1 eV between the two calculation methods, as shown in Figure S6 and Table S2 (Supporting Information).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…This process proceeds with a barrier of 0.67 eV to overcome the transition state (TS) located at an H−H separation distance of 1.05 Å. Our calculated barrier is in excellent agreement with recent constrained-AIMD calculations by Kronberg and Laasonen, 48 in which the barrier for the Tafel mechanism exhibits a coverage dependence, decreasing from 0.80 eV (0.66 ML) to 0.53 eV (1.00 ML). To validate the reliability of our calculated free energy, we compare the HDNN with AIMD simulations, resulting in a mean averaged error (MAE) of ∼0.1 eV between the two calculation methods, as shown in Figure S6 and Table S2 (Supporting Information).…”
supporting
confidence: 88%
“…The inverse behavior is predicted for the Tafel mechanism barrier, which has been shown to increase at lower coverage. 48 This is significant, as it suggests the dual mechanistic nature for HER on Pt(111) which is highly coverage-dependent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that the configuration of deprotonated H2O at final state is not as usual as previous report about metal catalyst. 67 Specifically, one hydrogen atom of H2O is pointed to the adsorbed hydrogen rather than the O atom of H2O from our observation (Figure 5a). This is owing to that the adsorbed H is actually negatively charged by -0.17 |e| and thus have strong affinity to hydrogen atom of H2O.…”
Section: Resultsmentioning
confidence: 54%
“…18 This finding, however, contrasts with the most recent DFT studies for the HER over Pt(111), reporting that the active hydrogen species is bonded weakly when considering the aqueous electrolyte by means of implicit or explicit solvation approaches (ΔG H of about 200 to 400 meV). 19,20 The author ascribed these differences to a type II error. 21 The Sabatier principle in its thermodynamic form at zero overpotential purports thermoneutral bonding as the optimum situation for a twoelectron process.…”
mentioning
confidence: 99%